Enhancing Student Satisfaction through Facilities, Administration, and Academic Services: A Systematic Review - Yusuf, Trisna Kusuma; Sowiyah, Sowiyah; Sari, Siti Rahma; Dermawan, Oki (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to examine the relationship between the quality of academic facilities, the effectiveness of administrative management, academic services, and student satisfaction in higher education through a systematic literature review. Student satisfaction is a crucial indicator of higher education quality and is influenced not only by teaching and lecturer–student interactions but also by the availability of adequate academic facilities and effective administrative systems. This study reviewed 20 peer-reviewed journal articles published between 2019 and 2024, sourced from Google Scholar and SINTA, and selected based on predefined inclusion criteria related to higher education and student satisfaction. The findings indicate that high-quality academic facilities—such as classrooms, laboratories, libraries, and supporting information technology—have a significant positive impact on students’ learning experiences and satisfaction. In addition, effective administrative management characterized by efficiency, responsiveness, transparency, and the use of academic information systems plays a vital role in enhancing student satisfaction. The review also reveals that the interaction between academic facilities quality and administrative effectiveness creates a cumulative effect in improving student satisfaction. These findings provide valuable insights for higher education institutions in optimizing facilities, strengthening administrative services, and implementing effective academic information systems to enhance overall student satisfaction.